PENGARUH MODIFIKASI SUHU PEMANASAN PADA KUALITAS CAMPURAN GLASIR BASALT UNTUK KERAMIK TEMBIKAR - Birawidha, David Candra; Amanda, Jihan Fhara; Syafriadi; Amin, Muhammad; Yanti, Evi Dwi; Pratiwi, Indah; Jannah, Wirdatul (Indonesian Mining Journal, 2023)
Research has been conducted on the effect of temperature variations on basalt-based glaze mixtures for stoneware ceramic applications using temperature variations of 1100, 1200, and 1300°C. This research aims to determine the optimum temperature for the best quality basalt glaze. The glaze sample was made using raw materials of asalt, kaolin, and feldspar their composition around 60%, 10%, and 30% wts respectively performing their grain sizes under 100 mesh. Material characterization was carried out by analyzing their XRF, XRD, and optical microscopy. At a burning temperature of 1200oC, the basalt-based glaze mixture significantly influences the structure and changes of glaze on the surface of the specimen from a macro-structural perspective. At the temperature of 1200°C, the glaze layer has reached the perfect melting point and coats the specimen surface evenly and results in not easily cracked and broken. It was proven that the glaze liquid could penetrate the pores, completely covering the surface morphology of the test object. Regarding the multitude of colors formed at temperature of 1200°C, it can optimize the content of dye metals such as iron, manganese, and cobalt in the glaze materials.